PVC master batch as well as preparation method and application thereof
By adding type II anhydrous gypsum and impact-resistant additives to the PVC resin, the problem of insufficient impact resistance of PVC materials is solved, and a significant improvement in material performance has been achieved.
Patent Information
- Application Number
- CN202411734856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-22
AI Technical Summary
The existing PVC materials have shortcomings in impact resistance, and calcium carbonate is poor in compatibility as a common additive in PVC systems, making it difficult to disperse well, affecting the performance of the material.
By adding 20-50 parts of Type II anhydrous gypsum (particle size ≥800 mesh, ignition loss of 0.2-0.4%), 2-3 parts of impact aid and 10-20 parts of stabilizer to the PVC resin, the impact resistance of PVC materials is improved.
It effectively improves the impact resistance of PVC materials, improves the dispersion and compatibility of anhydrous gypsum in PVC resin, and improves the overall strength and processing flowability of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial plastics, and in particular to a PVC masterbatch and a preparation method and application thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a commonly used polymer material, which is a thermoplastic polymer formed by the polymerization of vinyl chloride monomer. Since PVC resin raw materials are widely available, inexpensive, and have excellent comprehensive properties, such as good physical, mechanical, chemical, and electrical insulation properties, PVC masterbatch prepared from PVC resin as the matrix has a wide range of applications, such as the preparation of cable pipes, packaging boxes, PVC pipes, automotive plastic PP, agricultural greenhouses, resin tiles, SPC floors, etc. However, the prepared materials have problems such as impact resistance.
[0003] In order to improve the impact resistance of PVC materials, the relevant technology usually adds some calcium carbonate to the PVC system. Although it can improve the heat resistance, wear resistance, dimensional stability and stiffness of the products, calcium carbonate itself has poor compatibility with PVC resin, and calcium carbonate particles are easy to agglomerate and cannot be well dispersed in the PVC system, which affects the effect of improving the impact resistance of PVC materials.
[0004] Therefore, it is urgent to provide a PVC material with good impact resistance. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a PVC masterbatch and a preparation method and application thereof, aiming to solve the technical problem of how to improve the impact resistance of PVC materials.
[0006] In the first aspect, an embodiment of the present application provides a PVC masterbatch, comprising the following components in parts by weight: 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additives, and 10-20 parts of stabilizers; wherein the anhydrous gypsum is type II anhydrous gypsum, and the particle size of the type II anhydrous gypsum is ≥800 mesh, and the loss on ignition is 0.2-0.4%.
[0007] In the technical solution of the embodiment of the present application, the advantage of anhydrous gypsum having good dispersibility in PVC resin is utilized to compound anhydrous gypsum with PVC resin, and with the assistance of impact-resistant additives and stabilizers, the impact resistance of the PVC material can be effectively improved.
[0008] In some embodiments, the mass ratio of anhydrous gypsum to PVC resin is (25-30):100.
[0009] In this embodiment, the amount of anhydrous gypsum affects the degree of improvement of the impact resistance of the PVC material. As the amount of anhydrous gypsum increases, the degree of improvement of the impact resistance first increases and then decreases. It can be understood that an appropriate amount of anhydrous gypsum can accelerate the hydration rate and improve the impact resistance of the material, but excessive anhydrous gypsum will cause the hydration process to be too fast, which will have a limited improvement in the impact resistance of the material. Within the limited range of this embodiment, the impact resistance of the prepared PVC masterbatch is greatly improved.
[0010] In some embodiments, anhydrous gypsum is prepared by using phosphate rock powder as raw material through a liquid phase crystallization method.
[0011] In this embodiment, the anhydrous gypsum obtained by the liquid phase crystallization method is type II anhydrous gypsum. The particle size of type II anhydrous gypsum is small, so type II anhydrous gypsum has good compatibility with PVC, which is beneficial to the improvement of the impact strength of PVC materials; at the same time, the anhydrous gypsum obtained by the liquid phase crystallization method has the characteristics of low ignition loss, that is, low impurity content, and high-purity anhydrous gypsum can be more evenly dispersed in the PVC matrix and form a stronger interaction force with the PVC polymer chain, thereby helping to improve the overall strength of the PVC masterbatch, and the high-purity anhydrous gypsum helps to improve the processing fluidity of PVC, so that the PVC masterbatch is easier to form a uniform structure during the processing, which is beneficial to improve the impact resistance of the PVC masterbatch.
[0012] In some embodiments, the PVC masterbatch further comprises the following components: 1-5 parts of a coupling agent, based on weight.
[0013] In this embodiment, the coupling agent is used to modify the anhydrous gypsum to improve the compatibility and dispersibility of the anhydrous gypsum with the PVC resin, which is beneficial to the improvement of the impact resistance of the PVC masterbatch; the reason why the coupling agent can improve the compatibility of the anhydrous gypsum with the PVC resin is that the coupling agent molecule contains a hydrophilic group and a lipophilic group. This structure enables the coupling agent to chemically react or physically adsorb with the anhydrous gypsum and the PVC molecular chain at the same time, thereby reducing the surface tension between the anhydrous gypsum and the PVC resin, and forming a strong chemical bond or physical bond between the two, thereby improving the compatibility.
[0014] In some embodiments, the coupling agent includes one or more of an aluminum coupling agent, a silane coupling agent, and a titanate coupling agent.
[0015] In this embodiment, aluminum coupling agent, silane coupling agent and titanate coupling agent all have the effect of improving the impact resistance of PVC masterbatch; preferably, the coupling agent is an aluminum coupling agent, which, in addition to the coupling effect, can also significantly reduce the viscosity of the PVC system, inhibit the coagulation between anhydrous gypsum, and improve the dispersibility of anhydrous gypsum, thereby increasing the filling amount to further improve the impact resistance of the PVC masterbatch.
[0016] In some embodiments, the stabilizer includes one or more of calcium stearate, zinc stearate, lead stearate, and barium stearate.
[0017] In this embodiment, the stabilizer can prevent the degradation and discoloration of the PVC masterbatch during the processing, and can enhance the water resistance of the anhydrous gypsum, while ensuring the stability of the anhydrous gypsum and the PVC resin raw materials, which is beneficial to the improvement of the impact resistance of the PVC masterbatch; preferably, in some embodiments, the stabilizer is calcium stearate, and the crystallinity of calcium stearate is beneficial to increase the hardness of the anhydrous gypsum, which is beneficial to further improve the impact strength of the PVC masterbatch after the PVC masterbatch is prepared.
[0018] In some embodiments, the impact-resistant additive includes one or more of chlorinated polyethylene, acrylic copolymer, and methyl methacrylate-butadiene-styrene copolymer.
[0019] In this embodiment, the impact-resistant additive improves the impact resistance of the PVC masterbatch by improving the toughness, ductility and impact strength of the PVC masterbatch; preferably, the impact-resistant additive is chlorinated polyethylene (CPE), which has good compatibility with PVC and is more conducive to improving the impact resistance of the PVC masterbatch.
[0020] In the second aspect, an embodiment of the present application provides a method for preparing a PVC masterbatch, comprising the following steps: providing a plurality of raw materials, and mixing the plurality of raw materials evenly to obtain a mixture; mixing and extruding the mixture through a twin-screw extruder and cooling and pelletizing the mixture to obtain a PVC masterbatch; wherein, in parts by mass, the plurality of raw materials include 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additives, 10-20 parts of stabilizers and / or 1-5 parts of coupling agents.
[0021] In the technical solution of the embodiment of the present application, the air and water isolation effect of the PVC resin is beneficial to maintaining the chemical stability and dispersion uniformity of other components in the PVC masterbatch, and can improve the production efficiency of plastic products and reduce costs.
[0022] In some embodiments, the process parameters of the twin-screw extruder are: heating zone 1 at 100-120°C, heating zone 2 at 120-150°C, heating zone 3 at 120-150°C, and heating zone 4 at 130-170°C.
[0023] In this embodiment, within the temperature range of zone 1, each component is transformed into a glassy state, and the temperature ranges of zones 2 and 3 are kept warm to ensure that the infusible components are solidified. After the temperature of zone 4 is cooled, PVC masterbatch is finally obtained. The prepared PVC masterbatch has high uniformity and good impact resistance.
[0024] In a third aspect, an embodiment of the present application provides an application of a PVC masterbatch in the preparation of a plastic product.
[0025] In this embodiment, since the plastic product contains the above-mentioned PVC masterbatch, the plastic product has excellent impact resistance and can be applied to the preparation of plastic products such as cable pipes, packaging boxes, PVC pipes, automotive plastic PP, agricultural greenhouses, resin tiles, SPC floors, etc.
[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0027] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0029] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0031] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0032] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0033] In the description of the embodiments of the present application, technical terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", and "circumferential" indicate orientation or positional relationships, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present application.
[0034] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0035] In order to improve the impact resistance of PVC materials, the related technology usually adds some calcium carbonate to the PVC system. Although it can improve the heat resistance, wear resistance, dimensional stability and rigidity of the product, calcium carbonate itself has poor compatibility with PVC resin, and calcium carbonate particles are easy to agglomerate and cannot be well dispersed in the PVC system, which affects the effect of improving the impact resistance of PVC materials. Therefore, it is necessary to provide a PVC material with good impact resistance.
[0036] In order to solve the technical problem of improving the impact resistance of PVC materials, the present application provides a PVC masterbatch and its preparation method and application. Plastic products containing the above PVC masterbatch have excellent impact resistance and can be used in the preparation of plastic products such as cable pipes, packaging boxes, PVC pipes, automotive plastic PP, agricultural greenhouses, resin tiles, SPC floors, etc.
[0037] In the first aspect, the present application provides a PVC masterbatch, comprising the following components in parts by weight: 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additives, and 10-20 parts of stabilizers; wherein the anhydrous gypsum is type II anhydrous gypsum, and the particle size of the type II anhydrous gypsum is ≥800 mesh, and the loss on ignition is 0.2-0.4%.
[0038] In the technical solution of the embodiment of the present application, the advantage of anhydrous gypsum having good dispersibility in PVC resin is utilized, anhydrous gypsum is compounded with PVC resin, and with the assistance of impact-resistant additives and stabilizers, the impact resistance of PVC masterbatch can be effectively improved; wherein, the low particle size and low impurity content of anhydrous gypsum are conducive to the dispersion of anhydrous gypsum in PVC resin, thereby improving the impact resistance of PVC masterbatch; specifically, in the present application, the particle size of type II anhydrous gypsum is 800 mesh, 1000 mesh, 1340 mesh, 2000 mesh or any value greater than 800 mesh, and the loss on ignition is 0.2%, 0.3%, 0.4% or any point value in the range of 0.2-0.4%.
[0039] Further, in some embodiments, the mass ratio of anhydrous gypsum to PVC resin is (25-30): 100. For example, the mass ratio of anhydrous gypsum to PVC resin can be any ratio within the range of 25:100, 28:100, 30:100 or (25-30):100; preferably, the mass ratio of anhydrous gypsum to PVC resin is 25:100.
[0040] In the technical solution of the embodiment of the present application, the amount of anhydrous gypsum affects the degree of improvement of the impact resistance of the PVC material. As the amount of anhydrous gypsum increases, the degree of improvement of the impact resistance first increases and then decreases. Understandably, an appropriate amount of anhydrous gypsum can accelerate the hydration rate and improve the impact resistance of the material, but excessive anhydrous gypsum will cause the hydration process to be too fast, which will have a limited improvement on the impact resistance of the material.
[0041] Furthermore, in some embodiments, anhydrous gypsum is prepared by liquid phase crystallization method using phosphate rock powder as raw material. Specifically, the preparation method of anhydrous gypsum is to add sulfuric acid to the solid-liquid mixed system of calcium sulfate dihydrate produced by phosphate rock acid leaching with sulfuric acid, and obtain anhydrous gypsum through crystallization reaction. The preparation method directly uses the solid-liquid mixed system in the production of wet phosphoric acid as raw material, wherein a large amount of metal salts and the remaining sulfuric acid formed by acid hydrolysis of phosphate rock powder are not filtered, washed and lost, and can directly act as nucleating agents and crystallization agents in the crystallization process, thereby promoting the crystallization of calcium sulfate dihydrate to anhydrous calcium sulfate.
[0042] Specifically, the preparation method of anhydrous gypsum can be: using phosphate rock powder as a raw material, and adding it to a reactor with an appropriate amount of sulfuric acid solution; wherein: the liquid-solid ratio of the sulfuric acid solution to the phosphate rock powder in the reaction system is controlled to be 1-5L:1kg; after reacting at 80°C for 1h, an acid leaching system containing calcium sulfate dihydrate is formed; thereafter, sulfuric acid is added to the acid leaching system, and a crystallization reaction is carried out at 80-100°C for 1-3h, and the mass concentration of sulfuric acid in the system after the crystallization reaction is completed is 25-30%; the product after the reaction is completed is filtered and washed conventionally to obtain anhydrous calcium sulfate.
[0043] In the technical solution of the embodiment of the present application, the anhydrous gypsum obtained by the liquid phase crystallization method is type II anhydrous gypsum. The particle size of type II anhydrous gypsum is small, which can increase the interaction between type II anhydrous gypsum and PVC resin, which is beneficial to the improvement of the impact strength of PVC masterbatch; at the same time, the obtained type II anhydrous gypsum has the characteristics of low loss on ignition, that is, low impurity content, and high-purity type II anhydrous gypsum can be more evenly dispersed in the PVC matrix and form a stronger interaction force with the PVC polymer chain, thereby helping to improve the overall strength of the PVC masterbatch, and high-purity anhydrous gypsum may help to improve the processing fluidity of PVC, so that the PVC masterbatch is easier to form a uniform structure during the processing, which is beneficial to improve the impact resistance of the PVC masterbatch.
[0044] Further, in some embodiments, the PVC resin is a modified PVC resin to further improve the impact resistance of the PVC masterbatch, or to give the prepared PVC masterbatch other processing properties. Wherein, the modification method of the PVC resin includes but is not limited to the following steps: adding a modifier and a polyvinyl chloride resin to N,N-dimethylamide, ultrasonically mixing for 5-10 minutes, heating to 85-90°C for reaction for 1-2 hours, cooling to 20-30°C, adding methanol, stirring and mixing for 10-15 minutes, and filtering to obtain a crude modified polyvinyl chloride product; adding tetrahydrofuran to the crude modified polyvinyl chloride product, ultrasonically mixing for 5-10 minutes, adding methanol, stirring and mixing for 10-15 minutes, filtering, and drying to obtain a modified polyvinyl chloride; wherein, the preparation method of the modifier includes adding methyl stearate and hexafluorodiamine to methanol, heating to 65-70°C, stirring and reacting for 12-15 hours, vacuum rotary evaporation for 1-3 hours, removing methanol and excess hexafluorodiamine, and obtaining a modifier.
[0045] Furthermore, in some embodiments, the PVC masterbatch further comprises, by weight, 1-5 parts of a coupling agent. For example, the content of the coupling agent may be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, or any value within the range of (1-5).
[0046] In the technical solution of the embodiment of the present application, the coupling agent is used to modify the anhydrous gypsum to further improve the compatibility and dispersibility of the anhydrous gypsum with the PVC resin, thereby facilitating the improvement of the impact resistance of the PVC masterbatch. The reason why the coupling agent can improve the compatibility of the anhydrous gypsum with the PVC resin is that the coupling agent molecules of the present application contain hydrophilic groups and lipophilic groups. This structure allows the coupling agent to chemically react or physically adsorb with the anhydrous gypsum and the PVC molecular chain at the same time, thereby reducing the surface tension between the anhydrous gypsum and the PVC resin, and forming a strong chemical bond or physical bond between the two, thereby improving the compatibility.
[0047] Further, in some embodiments, the coupling agent includes one or more of an aluminum coupling agent, a silane coupling agent, and a titanate coupling agent. Among them, the silane coupling agent includes one or more of KH560, KH-570, and KH-550; the aluminum coupling agent includes an aluminate coupling agent.
[0048] In the technical solution of the embodiment of the present application, aluminum coupling agents, silane coupling agents, and titanate coupling agents all have the effect of improving the impact resistance of PVC masterbatch. Preferably, the coupling agent is an aluminum coupling agent, which, in addition to the coupling effect, can also significantly reduce the viscosity of the PVC system, inhibit the coagulation between anhydrous gypsum, and improve the dispersibility of anhydrous gypsum, thereby increasing the filling amount to further improve the impact resistance of the PVC masterbatch.
[0049] Furthermore, in some embodiments, the stabilizer includes one or more of calcium stearate, zinc stearate, lead stearate, and barium stearate.
[0050] In the technical solution of the embodiment of the present application, on the one hand, the stabilizer can prevent the degradation and discoloration of the PVC masterbatch during the processing, and on the other hand, the stabilizer can enhance the water resistance of the anhydrous gypsum, while ensuring the stability of the anhydrous gypsum and the PVC resin raw materials, which is beneficial to the improvement of the impact resistance of the PVC masterbatch. Preferably, in some embodiments, the stabilizer is calcium stearate, and the crystallinity of calcium stearate is beneficial to increase the hardness of the anhydrous gypsum, which is beneficial to further improve the impact strength of the PVC masterbatch after the PVC masterbatch is prepared.
[0051] Furthermore, in some embodiments, the impact-resistant additive includes one or more of chlorinated polyethylene, acrylic copolymer, and methyl methacrylate-butadiene-styrene copolymer.
[0052] In the technical solution of the embodiment of the present application, the impact-resistant additive improves the impact resistance by improving the toughness, ductility and impact strength of the PVC material. Preferably, the impact-resistant additive is chlorinated polyethylene (CPE), which has good compatibility with PVC and is more conducive to improving the impact resistance of the PVC masterbatch.
[0053] In a second aspect, the present application provides a method for preparing a PVC masterbatch, comprising the following steps: providing a plurality of raw materials, and mixing the plurality of raw materials evenly to obtain a mixture; mixing and extruding the mixture through a twin-screw extruder, and cooling and pelletizing the mixture to obtain a PVC masterbatch; wherein, in parts by mass, the plurality of raw materials include 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additives, 10-20 parts of stabilizers and / or 1-5 parts of coupling agents.
[0054] In the technical solution of the embodiment of the present application, the air and water isolation effect of the PVC resin is beneficial to maintaining the chemical stability and dispersion uniformity of other components in the masterbatch, and can improve the production efficiency of plastic products and reduce costs.
[0055] Further, in some embodiments, the process parameters of the twin-screw extruder are: heating zone 1 at 100-120°C, heating zone 2 at 120-150°C, heating zone 3 at 120-150°C, and heating zone 4 at 130-170°C.
[0056] In the technical solution of the embodiment of the present application, within the temperature range of zone one, each component is transformed into a glassy state, and insulation is performed within the temperature ranges of zones two and three to ensure that the infusible components are solidified. After the temperature in zone four is cooled, PVC masterbatch is finally obtained. The prepared PVC masterbatch has high uniformity and good impact resistance.
[0057] In a third aspect, the present application provides an application of a PVC masterbatch in the preparation of plastic products.
[0058] In the technical solution of the embodiment of the present application, since the plastic product contains the above-mentioned PVC masterbatch, the plastic product has excellent impact resistance and can be applied to the preparation of plastic products such as cable pipes, packaging boxes, PVC pipes, automotive plastic PP, agricultural greenhouses, resin tiles, SPC floors, etc.
[0059] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0060] 1. Preparation method Source of raw materials In the present application, the preparation method of anhydrous gypsum is as follows: phosphate rock powder is used as a raw material, and an appropriate amount of sulfuric acid solution is added to a reactor; wherein: the liquid-solid ratio of sulfuric acid solution to phosphate rock powder in the reaction system is controlled to be 5L:1kg; after reacting at 80°C for 1h, an acid leaching system containing calcium sulfate dihydrate is formed; sulfuric acid is added to the acid leaching system, and a crystallization reaction is carried out at 100°C for 1h, and the mass concentration of sulfuric acid in the system after the crystallization reaction is 25%; the product after the reaction is conventionally filtered and washed to obtain anhydrous calcium sulfate. According to the provisions of GB / T5484-2012 "Chemical Analysis Method for Gypsum", the crystal water content of the obtained anhydrous calcium sulfate is measured to be 0.3%, the anhydrous gypsum is type II anhydrous gypsum, the particle size is 1000 mesh, and the ignition loss is 0.26%.
[0061] Example 1 A PVC masterbatch comprises the following components in parts by mass: 25 parts of anhydrous gypsum, 100 parts of PVC resin, 3 parts of chlorinated polyethylene, and 10 parts of calcium stearate.
[0062] A preparation method of PVC masterbatch comprises the following steps: mixing anhydrous gypsum, PVC resin, chlorinated polyethylene and calcium stearate in a high-speed mixer at 8000 rpm for 30 seconds according to mass parts, continuously adding the uniformly mixed materials to the feed port of a twin-screw extruder, setting the temperature of each temperature zone of the twin-screw extruder as follows: heating zone 1 at 100°C, heating zone 2 at 120°C, heating zone 3 at 150°C and heating zone 4 at 170°C, and continuously extruding cold-drawn strips for granulation to obtain the PVC masterbatch.
[0063] Embodiment 2-7 A PVC masterbatch, other contents are the same as those of Example 1, except that the amounts of anhydrous gypsum are 10 parts, 20 parts, 30 parts, 40 parts, 50 parts and 60 parts, respectively.
[0064] Embodiment 8-11 A PVC masterbatch, other contents are the same as those of Example 1, except that the amounts of chlorinated polyethylene are 0 part, 1 part, 2 parts and 4 parts respectively.
[0065] Examples 12-15 A PVC masterbatch, other contents are the same as those of Example 1, except that the amount of calcium stearate is 0 parts, 5 parts, 20 parts and 30 parts.
[0066] Examples 16-17 A PVC masterbatch, the other contents are the same as those of Example 1, except that a silane coupling agent is added, and the amounts of the silane coupling agent are 5 parts and 10 parts, respectively.
[0067] Comparative Example 1 A PVC masterbatch, other contents of which are the same as those of Example 1, except that anhydrous gypsum is not included.
[0068] Comparative Example 2 A PVC masterbatch, other contents of which are the same as those of Example 1, except that anhydrous gypsum is replaced by calcium carbonate.
[0069] Comparative Example 3 A PVC masterbatch, other contents of which are the same as those of Example 1, except that anhydrous gypsum is replaced by α-gypsum.
[0070] Comparative Example 4 A PVC masterbatch, other contents of which are the same as those of Example 1, except that the impact-resistant additive is replaced with a styrene-butadiene-styrene ternary block copolymer.
[0071] Comparative Example 5 A PVC masterbatch, other contents of which are the same as those of Example 1, except that the stabilizer is replaced with dibutyltin dilaurate.
[0072] 2. Test Method 1. According to GB / T14152-2001, the PVC masterbatch obtained in each embodiment and comparative example was tested for impact resistance after injection molding. The test results are shown in Table 1.
[0073] Table 1 Impact resistance test results
[0074] II. Analysis of test results of various embodiments and comparative examples It can be seen from the results of Examples 1-7 in Table 1 that the impact strength, tensile strength and flexural strength of the PVC masterbatch first increase and then decrease with the increase in the amount of anhydrous gypsum. When the amount of anhydrous gypsum accounts for 25% of the mass of the PVC resin, the impact resistance is optimal; it can be seen from the results of Examples 1 and 8-11 in Table 1 that with the increase in the amount of impact additive, the impact strength and flexural strength of the PVC masterbatch show a trend of first increasing and then decreasing, while the flexural strength gradually decreases, indicating that excessive or insufficient impact additives will have a negative impact on the impact strength of the PVC masterbatch to a certain extent; it can be seen from the results of Examples 1 and 12-15 in Table 1 that with the increase in the amount of stabilizer, the impact strength of the PVC masterbatch shows a trend of first increasing and then decreasing, indicating that excessive or insufficient amounts of stabilizers will also be detrimental to the impact strength of the PVC masterbatch; it can be seen from the results of Examples 1 and 16-17 in Table 1 that the coupling agent can improve the impact strength, flexural strength and tensile strength of the material to a certain extent.
[0075] Furthermore, compared with Example 1, the impact strength, bending strength and tensile strength of the PVC masterbatch in Comparative Example 1 are greatly reduced, indicating that anhydrous gypsum has a positive effect on improving the impact strength of the PVC masterbatch; compared with Example 1, the impact strength of the PVC masterbatch in Comparative Example 2 is slightly reduced, and the cost of anhydrous gypsum is greatly reduced compared with calcium carbonate, indicating that the use of anhydrous gypsum in the preparation of PVC masterbatch in this application can effectively reduce production costs; compared with Example 1, the impact strength, bending strength and tensile strength of the PVC masterbatch in Comparative Example 3 are greatly reduced, the reason is that α gypsum is semi-hydrated gypsum with certain foaming properties, which leads to a decrease in impact resistance. It can be seen from Example 1 and Comparative Examples 4 and 5 that replacing the impact-resistant additives and stabilizers of this application will greatly reduce the impact resistance.
[0076] In summary, the technical solution of the present application utilizes the advantage of good dispersibility of anhydrous gypsum in PVC resin, compounds anhydrous gypsum with PVC resin, and with the assistance of impact-resistant additives and stabilizers, can effectively improve the impact resistance of PVC materials. Furthermore, plastic products using the above PVC masterbatch have excellent impact resistance and can be used in the preparation of plastic products such as cable pipes, packaging boxes, PVC pipes, automotive plastic PP, agricultural greenhouses, resin tiles, SPC floors, etc.
[0077] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A PVC masterbatch, characterized in that: The invention comprises the following components in parts by mass: 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additive, and 10-20 parts of stabilizer; wherein the anhydrous gypsum is type II anhydrous gypsum, and the particle size of the type II anhydrous gypsum is ≥800 meshes, and the loss on ignition is 0.2-0.4%.
2. The PVC masterbatch according to claim 1, characterized in that: The mass ratio of the anhydrous gypsum to the PVC resin is (25-30):
100.
3. The PVC masterbatch according to claim 1, characterized in that: The anhydrous gypsum is prepared by using phosphate rock powder as raw material through a liquid phase crystallization method.
4. The PVC masterbatch according to claim 1, characterized in that: Calculated by weight, the PVC masterbatch also includes the following components: 1-5 parts of coupling agent.
5. The PVC masterbatch according to claim 4, characterized in that: The coupling agent includes one or more of an aluminum coupling agent, a silane coupling agent, and a titanate coupling agent.
6. The PVC masterbatch according to claim 1, characterized in that: The stabilizer includes one or more of calcium stearate, zinc stearate, lead stearate and barium stearate.
7. The PVC masterbatch according to claim 1, characterized in that: The impact-resistant additive includes one or more of chlorinated polyethylene, acrylic copolymer, and methyl methacrylate-butadiene-styrene copolymer.
8. A method for preparing a PVC masterbatch according to any one of claims 1 to 7, characterized in that: The following steps are involved: Providing a plurality of raw materials, and uniformly mixing the plurality of raw materials to obtain a mixed material; The mixed material is mixed and extruded through a twin-screw extruder and pelletized after cooling to obtain the PVC masterbatch; Wherein, the multiple raw materials include, by weight, 20-50 parts of anhydrous gypsum, 100 parts of PVC resin, 2-3 parts of impact-resistant additive, 10-20 parts of stabilizer and / or 1-5 parts of coupling agent.
9. The preparation method according to claim 8, characterized in that: The process parameters of the twin-screw extruder are: heating zone 1 at 100-120°C, heating zone 2 at 120-150°C, heating zone 3 at 120-150°C, and heating zone 4 at 130-170°C.
10. Use of the PVC masterbatch according to any one of claims 1 to 7 in the preparation of plastic products.